The Future of Non-Fungible Tokens (NFTs): An Analysis of Regulatory and Compliance Challenges and Opportunities - Sulkis, Adam (Digital Repository of Theses, 2024)
Non-Fungible Tokens (NFTs) over the recent years have jumped into the limelight, making us rethink how we view owning physical or nonphysical items that have value to us. These so called ‘digital assets’ make us constantly question how we can own an intangible item of any sort, in an ever-evolving digital age. NFTs encompass virtually everything we can think of in regard to tangible items, but now intangible, such as contracts, paintings, land, video games, whom attract all of their accompanying creators, artists, facilitators, and collectors, especially for their ability to put the control and power of creation back into their creators hands. What accompanies all of this is a sense of uncertainty, particularly in the regulation and of such assets. Questions about who has the rights to any sort of intellectual property, laws around purchase and sale, and whether the market of NFTs is even legitimate, have all cropped up since the sudden surge of NFT interest starting in 2021. Despite the general pop culture idea that NFTs are just a meme to be mocked, there is still a need to implement some sort of regulatory framework. This framework would protect investors, reduce risk of investing in such assets, and squeeze out mal actors that seek to take advantage of the burgeoning sector. This is akin to the implementation of the US ‘blue sky law’ era 100 years ago, where laws were enacted to protect stock market investors. The following these will engage in various methods producing various results, that create a discussion, to analyze this unique area of digital investment and collectables’ regulation and compliance, which will reveal the complex nature of generating a safe investment realm for buyers, while simultaneously preserving the rights and overall creativity environment of NFT creators.